Halal Cosmetic Products: Do Knowledge and Religiosity Affect Consumers’ Attitude and Intention to Use? - Mohd Suki, Norazah; Mohd Suki, Norbayah (International Journal of Engineering and Technology, 2018)
The goal of this research is to examine the effect of knowledge and religiosity on consumersâ€™ attitude towards Halal cosmetic products. Furthermore, the influence between consumersâ€™ attitude and their intention to use Halal cosmetic products is also explored. The Partial Least Square-Structural Equation Modelling (PLS-SEM) approach supported by Smart-PLS 2.0 was employed to evaluate the hypothesized model. This study conveys a strong message to cosmetic companies, particularly the producers, retailers, and distributors of cosmetic products regarding the imperative to foster better knowledge among consumersâ€™ regarding Halal cosmetic products consumption. The path estimate results of the PLS-SEM approach revealed that attitude is the strongest predictor of consumersâ€™ intention to use Halal cosmetic products. By having a positive attitude towards Halal cosmetic products, consumersâ€™ always look for the Halal label when buying cosmetic products. This proposition is further strengthened when the people considered most important to them also use Halal cosmetic products. Further, it was revealed that they also hold a strong belief that using Halal cosmetic products is important to them, especially when the decision to use it is of their own choice. Further, consumersâ€™ attitude towards Halal cosmetic products was impacted by aspects such as knowledge and religiosity. This study also informs on the benefits of fostering better knowledge among consumersâ€™ regarding Halal cosmetic products consumption towards captivating more demand of product consumption from Muslim consumers. The possible direction for future research is also presented.Â Â